Choroidal physiology and primary angle closure disease - Zhang, Xiulan; Jonas, Jost B. (Survey of ophthalmology, 2015)
Primary angle closure disease (PACD), prevalent in Asian countries, is generally associated with a shallower anterior chamber, a shorter axial length, thicker lens, hyperopia, and female sex. Other physiologic factors, however, may be important, especially with regard to triggering acute primary angle closure. Thickening of the choroid has been demonstrated in untreated and treated, acute and chronic PACD eyes. Recently, there has been growing interest in studying the role of the choroid in the pathophysiology of PACD. The emergence of new imaging technology such as the enhanced depth imaging mode of spectral-domain optical coherence tomography and swept-source optical coherence tomography has contributed to understanding PACD pathologies. We summarize the functions of the choroid and choroidal changes in the pathogenesis of PACD, and discuss potential future developments.